Kaniššuwar. A Tribute to Hans G. Güterbock on his Seventy-Fifth Birthday, May 27, 1983 - Harry A. Hoffner, Jr., (Assyriological Studies, 1986)
185-188: Supplement to the Bibliography of Hans Gustav Güterbock, 1971-1984.